Alterações fisiológicas e morfológicas de sementes de arroz submetidas a pré-secagem e envelhecimento acelerado - Kleinpaul, Jéssica Andiara (2023)
Rice is used worldwide in human food, so there is a need to have seeds of genetic, sanitary, physical and physiological quality. The chemical composition and cracking of the seeds are influenced by the moisture gradient during or after drying, altering the quality of the seeds. Thus, the objective of this research was to evaluate the effect of pre-drying and accelerated aging treatments in rice seeds on physiological and morphological changes in rice seedlings. Three experiments were conducted in a completely randomized design at the Didactic and Seed Research Laboratory at the Federal University of Santa Maria. The cultivars IRGA 431 CL, IRGA 424 RI and Guri INTÁ CL were used with three lots per cultivar, from the 2019/2020 season. The seeds were submitted to pre-drying and accelerated aging. In article 1, the severity of cracked seeds was evaluated, as well as the physiological quality of the seeds through the tests: weight of a thousand seeds, moisture content, first count, germination, shoot and root length, shoot and root dry mass. from root. In article 2, the electrical conductivity test and the tetrazolium test were evaluated. In article 3, three lots of the cultivar IRGA 431 CL were used, using different temperatures to overcome seed dormancy and at each temperature the seeds remained for different periods in a forced air circulation oven. In the experiment of article 3, the first count, germination, root and shoot length were evaluated. The data obtained were submitted to analysis of variance and compared by means of the Scott-Knott test and by regression analysis in articles 1 and 2 and by response surface in article 3. In the present study, it was possible to evaluate the severity of cracks in seeds of cultivars IRGA 431 CL, IRGA 424 RI and Guri INTÁ CL. For the cultivars IRGA 431 CL, IRGA 424 RI and Guri INTÁ CL, the use of pre-drying at 45 °C in a forced air circulation oven, without accelerated aging, was what caused the highest percentage of cracks in the rice seeds of the three cultivars . For the cultivars IRGA 431 CL, IRGA 424 RI and Guri INTÁ CL, breaking dormancy with pre-drying at 45 °C in an oven with forced air circulation and accelerated aging for 72 or 96 h at 42 °C is recommended. The electrical conductivity can be indicated to evaluate the vigor of the cultivars IRGA 431 CL, IRGA 424 RI and Guri INTÁ CL. Through the tetrazolium test, the viability and vigor of the seeds of the cultivars IRGA 431 CL, IRGA 424 RI and Guri INTÁ CL can be evaluated. To overcome dormancy of seeds of the cultivar IRGA 431 CL in a forced air circulation oven, a temperature between 41 and 44 °C for a period of 95 h is more indicated.